GC-MS Determination of Bioactive Compounds of Polygonum glabrum (Wild). - R. Neelamegam*, B. Ezhilan and (Journal of Phytology, 2011)
In this study, the bioactive compounds of Polygonum glabrum have been evaluated using GC-MS. The chemical compositions of the whole plant ethanol extract of P. glabrum were investigated using Perkin-Elmer Gas Chromatography-Mass Spectrometry, while the mass spectra of the compounds found in the extract was matched with the National Institute of Standards and Technology (NIST) library. GC-MS analysis of P. glabrum whole plant ethanol extract revealed the existence of the ether compound –Propane 1,1-diethoxy- (64.86%), alkane compound -2-Heptane, 5-ethyl-2,4-dimethyl- (13.51%), sulphur compound –Tiophene-2-Carboxamide, N-(2-furfuryl)- (8.!!%), alcoholic compound -1,14-Tetradecanediol (5.41%), and plasticizer compounds -1,2-Benzenedicarboxylic acid, isodecyloctyl ester (5.41%) and 1,2,3-Benzenetriol (2.79%). The results of this study offer a base of using P. glabrum as herbal alternative for the synthesis of antimicrobial agents.